Effect of heat stress on some physiological characteristics of Awassi Sheep in Iraq (Journal of the College of Basic Education, 2022)
Thirty four growing male Awassi I sheep were used in an attempt to assess a useful heat tolerance index by using some physiological and biochemical changes due to solar radiation exposure. The changes in body temperature, hemoglobin, haematocrit, total body water, triiodothyronine and cortisol was found to be not correlated with body gain decrease due to heat stress. Therefore, it can not be used to predict heat adaptability in this study.